2023
DOI: 10.1080/20008066.2023.2171752
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-based treatments for childhood abuse-related post-traumatic stress disorder in adults: a health-economic evaluation

Abstract: Background: Prolonged exposure (PE) is an effective treatment for post-traumatic stress disorder (PTSD). Objective: This study aimed to analyse the cost-effectiveness of three exposure-based treatments in patients with childhood abuse-related PTSD. Method: A net–benefit analysis was conducted alongside a pragmatic randomized controlled trial with participants ( N = 149) randomized to three conditions: PE ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
4
2
Order By: Relevance
“…In contrast to the purported assumption that STAIR would increase day-to-day functioning by addressing interpersonal and emotion regulation problems (Haasija and Cloitre, 2015), the present results do not show the advantage of adding this treatment to EMDR therapy in terms of cost-effectiveness. In contrast to the study by Kullberg et al (2023), we found a significant difference in mean societal costs between phase-based and direct trauma-focused conditions, with higher societal costs for phase-based treatment. The costs for PE and STAIR-PE appeared to be much higher (€ 4,479 and € 4,464, respectively) than those for EMDR and STAIR-EMDR (€ 1,686 and € 2,436, respectively).…”
Section: Figurecontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the purported assumption that STAIR would increase day-to-day functioning by addressing interpersonal and emotion regulation problems (Haasija and Cloitre, 2015), the present results do not show the advantage of adding this treatment to EMDR therapy in terms of cost-effectiveness. In contrast to the study by Kullberg et al (2023), we found a significant difference in mean societal costs between phase-based and direct trauma-focused conditions, with higher societal costs for phase-based treatment. The costs for PE and STAIR-PE appeared to be much higher (€ 4,479 and € 4,464, respectively) than those for EMDR and STAIR-EMDR (€ 1,686 and € 2,436, respectively).…”
Section: Figurecontrasting
confidence: 99%
“…A recent study examined the cost-effectiveness of prolonged exposure (PE) therapy preceded by STAIR among patients with PTSD related to childhood abuse (Kullberg et al, 2023). Unfortunately, the researchers did not answer the question of whether the addition of STAIR to trauma-focused treatment leads to economic benefits because of the skills gained during the preparation phase.…”
mentioning
confidence: 99%
“…In contrast to the purported assumption that STAIR would increase day-to-day functioning by addressing interpersonal and emotion regulation problems (Haasija and Cloitre, 2015), the present results do not show the advantage of adding this treatment to EMDR therapy in terms of cost-effectiveness. In contrast to the study by Kullberg et al (2023), we found a significant difference in mean societal costs between phase-based and direct trauma-focused conditions, with higher societal costs for phase-based treatment. The costs for PE and STAIR-PE appeared to be much higher (€ 4,479 and € 4,464, respectively) than those for EMDR and STAIR-EMDR (€ 1,686 and € 2,436, respectively).…”
Section: Figurecontrasting
confidence: 99%
“…However, the QALY outcomes in the study by Mavranezouli et al were measured over a different period of time (3 years) than in our study (9 months), so in comparing both outcomes, many assumptions had to be made, which leaves much uncertainty. The QALY's gained with EMDR seem somewhat lower than those for Prolonged Exposure from the study by Kullberg et al (2023); however, also in this case, many assumptions had to be made.…”
Section: Figurementioning
confidence: 79%
See 1 more Smart Citation